Comparison of oral alendronate versus prednisolone in treatment of infants with vitamin D intoxication - BEREKET, ABDULLAH; GÜRAN, TÜLAY (WILEY, 2012)
Aim: The aim of this report was to compare the efficacy of oral alendronate versus prednisolone treatment in addition to conventional measures in infants with vitamin D intoxication. Methods: In six infants (aged 8.0 +/- 2.1 months) with vitamin D intoxication, time to achieve normocalcemia with prednisolone treatment (Group I, n = 4) or alendronate treatment (Group II, n = 4, two infants started treatment from the baseline and two after unsuccessful prednisolone treatment) in addition to intravenous hydration and diuretic therapy were compared. Results: Baseline serum calcium levels ranged between 3.8 and 4.77 mmol/L. In the prednisolone group, although two patients reached normocalcemia on 7th and 12th days of treatment, other two patients did not despite 23 and 15 days of treatment and therefore switched to alendronate treatment. The mean duration of prednisolone treatment in these four patients was 14.2 +/- 6.7 days (range 7-23). In the alendronate group, two patients who started treatment from the baseline achieved normocalcemia on the 5th day. Other two patients achieved normocalcemia 2 days after switching to alendronate. Thus, the mean time to reach normocalcemia after single oral alendronate administration was 3.5 +/- 1.7 days (range 2-5) (p < 0.01 versus Group I). Conclusion: Alendronate treatment achieves normocalcemia four times earlier than prednisolone treatment and shortens hospital stay in infants with vitamin D intoxication.
Keywords: Alendronate; Bisphosphonates; Hypercalcemia; Intoxication; Vitamin D; HYPERVITAMINOSIS-D; HYPERCALCEMIA; THERAPY; BISPHOSPHONATES; CHILDREN